1974
DOI: 10.1021/bi00707a010
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of native streptokinase and altered streptokinase isolated from a human plasminogen activator complex

Abstract: The properties of native streptokinase and streptokinase purified from the human plasminogen activator complex (altered streptokinase) have been compared. Native streptokinase possesses a molecular weight of 44,000 and a s°o,w value of 3.03 S whereas the values for altered streptokinase are 36,000 and 2.82 S, respectively. Native streptokinase possesses an amino-terminal isoleucine and a carboxylterminal lysine residue whereas altered streptokinase possesses an amino-terminal serine and a carboxyl-terminal lys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
54
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(59 citation statements)
references
References 33 publications
5
54
0
Order By: Relevance
“…This experiment demonstrated extensive degradation of the streptokinase to fragments of molecular weights comparable to those reported for streptokinase in complex with rabbit plasmin (24). Degradation was considerably more extensive than previously observed when streptokinase was reacted with human plasminogen (8). However, in these previous studies, the incubation time was only 2-5 min as contrasted to 30 min.…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…This experiment demonstrated extensive degradation of the streptokinase to fragments of molecular weights comparable to those reported for streptokinase in complex with rabbit plasmin (24). Degradation was considerably more extensive than previously observed when streptokinase was reacted with human plasminogen (8). However, in these previous studies, the incubation time was only 2-5 min as contrasted to 30 min.…”
Section: Resultsmentioning
confidence: 62%
“…Human plasminogen complexed to streptokinase resulted in much less degradation under these conditions (8). However, when studied at 30 min, we found that streptokinase was extensively degraded when in complex with human plasminogen.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Clearly, at incubation times of up to 30 min, during which the time-dependent activity changes of importance to this study are occurring, the only components present are SK and HPg. At longer times, the HPg remains intact while a slight degradation of SK occurs (16). Therefore, all events that take place on incubation of the two proteins, at least up to times of 90 min, that lead to the ionic-strength-related expression of amidolytic activity occur prior to the conversion of HPg to HPm within the complex.…”
Section: Resultsmentioning
confidence: 99%
“…Several fragments and modified forms of SK have been isolated previously (Brockway & Castellino, 1974;Siefring & Castellino, 1976;Jackson et al, 1986;Malke et al, 1987;Misselwitz et al, 1992;Rodriguez et al, 1994Rodriguez et al, , 1995Shi et al, 1994;Reed et al, 1995;Young et al, 1995). A number of SK fragments remain folded when isolated in solution and a minority maintain an ability to cause Plg activation, although, in most cases, this occurs at substantially reduced rates when compared with native SK.…”
mentioning
confidence: 99%